2015
DOI: 10.2147/copd.s77257
|View full text |Cite
|
Sign up to set email alerts
|

The COPD assessment test correlates well with the computed tomography measurements in COPD patients in China

Abstract: BackgroundThe chronic obstructive pulmonary disease (COPD) assessment test (CAT) is a validated simple instrument to assess health status, and it correlates well with the severity of airway obstruction in COPD patients. However, little is known about the relationships between CAT scores and quantitative computed tomography (CT) measurements of emphysema and airway wall thickness in COPD patients in the People’s Republic of China.MethodsOne hundred and twelve participants including 63 COPD patients and 49 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 16 , 20 Previous studies have shown that %LAA-950 has the strongest correlation with emphysema at both the macroscopic and microscopic levels among all the emphysema indicators measured by quantitative CT. 21 , 22 %LAA-950 is also the most common used parameter in previous studies. 14 , 16 , 20 For this reason, %LAA-950 was selected as the major indicator of pulmonary emphysema and defined it as “EI”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 20 Previous studies have shown that %LAA-950 has the strongest correlation with emphysema at both the macroscopic and microscopic levels among all the emphysema indicators measured by quantitative CT. 21 , 22 %LAA-950 is also the most common used parameter in previous studies. 14 , 16 , 20 For this reason, %LAA-950 was selected as the major indicator of pulmonary emphysema and defined it as “EI”.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative CT is a promising technique, because it has made repeated and noninvasive measurements of structural changes in the lungs possible. 13 , 14 Emphysema is characterized by areas of reduced attenuation coefficients in the lungs on CT. 15 The severity of emphysema is generally quantified as the percentage of “low attenuation area” (LAA) in the lungs with Hounsfield units (HU) less than a specific threshold (eg, −950 HU; %LAA-950). 16 Previous studies have demonstrated that the measurements of emphysema in quantitative CT correlate well with the visual scoring systems and pathology measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Chest computed tomography (CT) is widely used for evaluation of lung diseases and CT measurements correlated well with the COPD assessment test. 6 In addition, CT is a useful tool for thoracic vascular assessment. It could detect changes of small vessels, and these anomalies are important for clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the CAT scores correlated well with the measurements of quantitative CT. Not only can it assess status of health and disease, but it can also associate with the extent of emphysema and thickness of bronchial tube wall in Chinese COPD patients. 14 In any subtypes of patients, the CAT scores after treatment were significantly lower than that before the treatment, but phenotype E was lower than that of phenotype M. This shows that symptomatic improvement of patients with phenotype E with treatment of tiotropium bromide is superior to that of phenotype M. Fujimoto et al 15 also obtained similar result in 2011. In addition to emphysema, phenotype M shows more severe airway remodeling of tube wall thickening in pathological morphology and increased airway inflammation; after using the same medicine, phenotype E may have better improvement of pulmonary function and symptom than phenotype M. Interestingly, our previous study 9 found that phenotype M in response to therapeutic effects of budesonide–formoterol were significantly greater compared with phenotype E, and bronchial wall thickening may be a better predictor for the response to treatment with bronchodilator and corticosteroid.…”
Section: Discussionmentioning
confidence: 83%